Pharmacogenomics and personalised medicine (Henry Stewart Talks, 2026)
Pharmacogenomics in personalized medicine, Genetic variation in drug response, Genomic technology for tailored therapy, Clinical pharmacogenomics examples, Genetic biomarkers and predictive testing, Ethical challenges in implementation, Equity in pharmacogenomic testing, Routine healthcare integration